MUTU GIZI DAN TINGKAT KESUKAAN MINUMAN KOPI DEKAFOSIN INSTAN - . Tejasari; . Sulistyowati; . Djumarti; Roro Ayu Arum Sari (JURNAL AGROTEKNOLOGI, 2010)
Reducing caffeine was meant for improving health effect of drinking coffee. Meanwhile supplementation of functional food ingredient such inulin and fructooligosaccharides (FOS) in coffee beverage is expected for emerging health value of decaff coffee. Decaffosin instant coffee was formulated from decaffeinated coffee powder enriched with 27 % w/w inulin powder and 7 % fructooligosacharides (FOS). This study aims to identify nutritional quality and to evaluate the effect of inulin and FOS addition at the same time on preference level of Dekafosin instan coffee. The result of showed that Dekafosin instan coffee contain 5.04 % of water and 2.3 % of mineral. Total reducing sugar, sucrose, glucose, fructose and soluble dietary fiber content of the beverage are 30.83, 0.47, 2.8, 94.33 and 98.1 percentage, respectively. Meanwhile, caffeine and inulin content of the the beverage are 1.23 and 28.15 percentage. The statistical analysis proved that decaffeination and the supplementation of inulin and FOS did not influence on the preference level of Dekafosin instant coffee, as showing by the following value : preference level of colour (x² count = 17.397 < x² table = 18.549), aroma (x² count = 5.563 > x² table = 4.168) and taste (x² count = 11.413 < x² table = 14.684) wich has a significance value (p) > 5 percent. Therefore, based on this analysis data it can be concluded an addition of inulin and FOS did not influence preference level toward Dekafosin instant coffee beverage.Keywords : decaffeinated coffee, inulin, FOS, Dekafosin instant coffee beverage, nutritional quality, preference level